The Relationship Between Family Social Support and Dietary Compliance in Hypertensive Patients - Arif, Abd Manan; Widiyawati, Wiwik; Widiharti, Widiharti; Sari, Diah Jerita Eka (Universitas Muhammadiyah Gresik, 2024)
Background : Hypertension is a condition of systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg. Hypertension can be prevented and avoided with a healthy diet. Dietary arrangements in hypertensive patients really need family support so that patients are able to undergo the treatment process properly according to the doctor's recommendations. The purpose of this study is to analyze the relationship between family support and compliance with diabetes in hypertensive patients at the heart specialist polyclinic of Muhammadiyah Gresik Hospital. Method : The design of this study is a correlation with a population of 93 hypertension patients and the sample set is all 93 patients. The sampling technique uses total sampling. The study used questionnaires for diit compliance. This study uses the Chi Square Test. Results: Most of the hypertension patients who were treated at the cardiac specialist polyclinic of Muhammadiyah Gresik Hospital had good family social support as many as 71 patients (76.3%), sufficient family social support as many as 18 patients (19.3%) and insufficient family social support as many as 4 patients (4.4%), The results of the Chi Square test analysis of the research obtained a value of p=0.00 < 0.05, meaning that there was a relationship between social support and diit compliance in hypertension patients. Conclusion: There is a relationship between family social support and compliance with diabetes in hypertensive patients at the heart specialist polyclinic of Muhammadiyah Gresik Hospital. Keywords : Family Social Support, Diit Compliance, Hypertension,